2017
DOI: 10.20506/rst.36.3.2723
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of maedi-visna virus in Lebanon

Abstract: Maedi-visna (MV) is a chronic viral disease prevalent in adult sheep that is caused by a virus belonging to the small ruminant lentivirus group (SRLV). This disease is considered to affect the international trade of sheep and is classified in the World Organisation for Animal Health (OIE) list of notifiable animal diseases. Although maedi-visna virus (MVV) has been detected in many countries, no study on its occurrence has been carried out in Lebanon. For this purpose, a serological survey of infection with MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…with SRLV infection in sheep that are absent of our study because no public publications from those countries were found, or they did not fulfilled the inclusion criteria. On the contrary, from 2005 to 2019, China, Costa Rica, Iran, Morocco, and Pakistan have never reported SRLV infection to the OIE and India, Lebanon, Czech Republic, Syria, and Turkey appear as “disease absent” despite available scientific descriptions from all these countries [ 20 , 21 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 33 , 34 , 35 , 55 , 67 ]. First reports on SRLV infection in Brazil according to OIE are from 2017, whereas scientific publications already reported the disease in 2007 [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…with SRLV infection in sheep that are absent of our study because no public publications from those countries were found, or they did not fulfilled the inclusion criteria. On the contrary, from 2005 to 2019, China, Costa Rica, Iran, Morocco, and Pakistan have never reported SRLV infection to the OIE and India, Lebanon, Czech Republic, Syria, and Turkey appear as “disease absent” despite available scientific descriptions from all these countries [ 20 , 21 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 33 , 34 , 35 , 55 , 67 ]. First reports on SRLV infection in Brazil according to OIE are from 2017, whereas scientific publications already reported the disease in 2007 [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 N, number of animals tested; 2 CI 95%, 95% confidence interval; 3 I 2 , heterogeneity statistic; 4 N/A, not applicable; 5 [ 25 , 26 , 28 , 29 , 31 , 33 , 35 ]; 6 [ 11 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 45 , 47 , 48 , 49 , 51 , 54 , 55 ]; 7 [ 57 , 58 , 59 , 61 , 62 , 63 , 64 , 65 , 66 ]; 8 [ 67 , 69 , 71 , 72 , 73 , 74 , 75 ]. …”
Section: Figurementioning
confidence: 99%
“…VM is distributed in sheep industry across the globe and responsible for serious production loss. VM prevalence have been reported as 24.8% in Spain (Lago et al, 2012), 71% in Lebanon (Tabet et al, 2017), from 10.5 to 21.6% in Ethiopia (Ayalet et al, 2001), 28.8% in Germany (Huttner et al, 2017), from 20 to 60% in the UK (Ogden et al, 2019), 34.8% in Kosovo (Cana et al, 2020), and LIVESTOCK S T U D I E S from 3.3 to 96.7% in Canada (Heinrichs et al, 2017). In Turkey prevalence of VM was reported between 2.7 to 77.9% (Burgu and Toker, 1990;Yavru et al, 2012;Muz et al, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Visna/maedi (VM) has been reported in Europe 4 , 5 , North America 6 , South America 7 , Asia 8 , and Africa 9 , 10 . Only New Zealand and Australia are yet VM free, nonetheless, these countries are suffering from CAEV 11 .…”
Section: Introductionmentioning
confidence: 99%